The Influence of Dissemination Risks, Need for Operational Flexibility and Global Management Skills on Firms Modal Decision in Host Countries - Tan, Benjamin L. B. (Institutional Knowledge at Singapore Management University, 2001)
This paper examines how firms' modal choice is influenced by their exposure to dissemination risks, need for strategic control and possession of global management skills. A probabilistic model is specified. The following hypotheses are incorporated in the model: the probability of choosing a more advanced entry, ceteris paribus, is a function of (1) the risk-adjusted expected net benefits of a firm's possession of certain types of intangible, transportable assets; (2) parent company attributes that necessitate control over its strategic resources overseas; and (3) possession of certain global resources that are specific to the firm such that their effective internalization calls for higher entry mode. The models are estimated using polychotomous regression analysis. Results generally confirm that size and possession of some knowledge-based, firm-specific strategic assets, are significantly related to advanced entry modes. They also confirm that firms opt for higher entry mode to gain control of competitive pricing in the foreign markets.